Time-resolved measurement of interatomic Coulombic decay induced by to-photon double excitation of Ne2 - Takanashi, Tsukasa; Jabbari, Ghazal; Golubev, Nikolay V.; Cederbaum, Lorenz S.; Kuleff, Alexander I. (Physical review letters, 2017)
The hitherto unexplored two-photon doubly excited states [Ne∗(2p−13s)]2 were experimentally identified using the seeded, fully coherent, intense extreme ultraviolet free-electron laser FERMI. These states undergo ultrafast interatomic Coulombic decay (ICD), which predominantly produces singly ionized dimers. In order to obtain the rate of ICD, the resulting yield of Ne+2 ions was recorded as a function of delay between the extreme ultraviolet pump and UV probe laser pulses. The extracted lifetimes of the long-lived doubly excited states, 390(−130/+450) fs, and of the short-lived ones, less than 150 fs, are in good agreement with ab initio quantum mechanical calculations.